Protection and the Historical Situation: Australia - Anderson, Karl L. (Quarterly Journal of Economics, 1938)
I. Alleged special features of Australia's economic position, 87.— II. The argument based on the terms of trade, 89.— The question of elasticity of demand, 92.— III. The influence of diminishing returns in the primary industries, 97.— Average vs. marginal conditions, 99.— The infant industry argument, 100.—IV. Effect of protection on the distribution of the national income, 102.— Conclusions, 104.